A Walrasian Theory of Markets with Adverse Selection - Gale, Douglas (Review of Economic Studies, 1992)
The paper describes a Walrasian theory of markets with adverse selection and shows how refinements of equilibrium can be used to characterize uniquely the equilibrium outcome. Equilibrium exists under standard conditions. It is shown that, under certain conditions, a stable set exists and is contained in a connected set of equilibria. For generic models there exists a stable outcome, that is, all the equilibria in the stable set have the same outcome. These ideas are applied to markets with one-sided and two-sided uncertainty. Under standard monotonicity conditions, it is shown that the stable outcome is separating and implies a particular pattern of matches of buyers and sellers.